Protein acetylation and related potential therapeutic strategies in kidney disease - Xiang-yu Li; Ju-tao Yu; Yu-hang Dong; Xiao-yu Shen; Rui Hou; Man-man Xie; Jie Wei; Xiao-wei Hu; Ze-hui Dong; Run-run Shan; Juan Jin; Wei Shao; et al. (Elsevier, 2023)
Kidney disease can be caused by various internal and external factors that have led to a continual increase in global deaths. Current treatment methods can alleviate but do not markedly prevent disease development. Further research on kidney disease has revealed the crucial function of epigenetics, especially acetylation, in the pathology and physiology of the kidney. Histone acetyltransferases (HATs), histone deacetylases (HDACs), and acetyllysine readers jointly regulate acetylation, thus affecting kidney physiological homoeostasis. Recent studies have shown that acetylation improves mechanisms and pathways involved in various types of nephropathy. The discovery and application of novel inhibitors and activators have further confirmed the important role of acetylation. In this review, we provide insights into the physiological process of acetylation and summarise its specific mechanisms and potential therapeutic effects on renal pathology.